PENGENALAN KETERAMPILAN LITERASI DIGITAL PADA KELOMPOK B TKS NURUL IMAN CARENANG - Afifah Afifah (Jurnal Anak Bangsa, 2024)
The use of digital media is very common in society, also in early childhood. The influence of digital media use really depends on the user's ability to filter various information presented in the media. The ability needed to reduce these negative impacts is to improve digital skills, so the aim of this research is to find out whether TKS teachers already have the ability to use digital media. adopting digital literacy. skills for their children by: (1) inviting parents to help children use devices, (2) teaching children to think critically in using media, and (3) introducing various types of media. This research targets formal and informal kindergarten teachers in Carenang sub-district using quantitative descriptive research methods. The results of this research show that as many as 92% of survey respondents introduced digital literacy to their children, this shows positive things about efforts to introduce digital literacy in Pontianak City at the Kindergarten level